Algunos apuntes para una estética literaria según Juan León Mera: entre romanticismo y neoclasicismo (Estudios) - Puig Peñalosa, Xavier (2018)
The article examines Juan León Mera’s ideas on literary aesthetics and how he proposed establishing a canon for the Ecuadorian literature of his age. This initiative drew from both the postulates of the aesthetics of Romanticism and those belonging to Neoclassical poetry. The present article elucidates which categories of both movements were used by Mera in his essays and correspondence, as the basis for his syncretic approach.